Disentangling Radiative Versus Non‐Radiative Controls on Urban Evapotranspiration Under Global Warming - Congyuan Li; Wenjing Zhao; Kaijun Ren; Ning Zhang; Xin Miao; Zhengcheng Song; Yuanshuo Zhang (Geophysical Research Letters)
Abstract As the nexus of terrestrial water‐energy‐carbon exchange, evapotranspiration (ET) modulates ecosystem‐climate interactions, yet its biophysical responses to urbanization and climate change remain unclear. Using fully coupled Earth system modeling and flux tower observations, we disentangle radiative (surface available energy) and non‐radiative (advection‐sustained vapor gradients) controls on global ET. The decoupling factor, a pivotal biophysical regulator of land‐atmosphere coupling for ET, exhibits a climate‐vegetation latitudinal gradient spanning 0.1 (arid) to 0.5 (continental). Global warming enhances land‐atmosphere coupling, suppressing radiative contributions while amplifying non‐radiative influences. Urbanization reduces ET but tends to shift its dominant driver toward available energy, unlike rural areas dominated by advection‐sustained vapor gradients. The urban‐rural contrast in the radiative contributor intensifies at ∼0.3 W m−2 decade−1 (2.4 times that of the non‐radiative contributor) under RCP8.5, linked to a 60% slower decline in urban decoupling factor than rural areas. This study provides a fuller picture of the mechanistic understanding of ET.